PEMBERIAN VCO UNTUK MENINGKATKAN KADAR eNOS (STUDI PADA TIKUS WISTAR DENGAN DIET TINGGI LEMAK) - Fitrianingsih Fitrianingsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
The aim of this study was proving the ability of VCO in increasing eNOS levels in Wistar rats fed HFD. This study used 25 male wistar rats were divided negative control is receiving with a normal diet, positive control receiving HFD, three treatment groups receiving a combination of HFD with VCO in dose of 1ml, 1,2 ml or 2 ml/day in period of 60 days. The blood taken from the eyes of rats and after end of this eNOS measurement done by using ELISA. The mean levels of eNOS group negative control, positive control, treatment 1,2, and 3 respectively are (1.95 ; 1.39 ; 1.47 ; 2.11 ; 2.55). The mean levels is higher than the group positive control but based on the results of One-Way ANOVA test showed that there were no significant differences in the mean levels of eNOS among all group treatment groups (p=0.305). VCO was not significantly increasing eNOS levels in HFD Wistar rats.